Sustaining Reforms for Inclusive Growth in Cameroon : A Development Policy Review - Charlier, Florence (World Bank, 2012)
Cameroon faces a challenging policy agenda over the next few years. The Government has been implementing its comprehensive poverty reduction strategy since April 2003. The Poverty Reduction Strategy Paper (PRSP) set an ambitious agenda for broad-based economic development with specific medium-term targets as well as detailed sector policies and programs for accelerating economic growth, strengthening the social sectors, and halving poverty over the following ten years. Despite a strong start, implementation of the PRSP slowed during the 2003-04 presidential election period, when fiscal discipline was relaxed and the restructuring of key public enterprises slowed. This faltering progress translated into much lower fiscal performance relative to program targets, higher government spending to prop up distressed key public enterprises, and the accumulation of domestic arrears. These developments led the International Monetary Fund (IMF) to declare Cameroon's Poverty Reduction and Growth Facility (PRGF) program off track in the third quarter of 2004, delaying attainment of the Heavily Indebted Poor Countries (HIPC) completion point by nearly two years. In the aftermath of the election, the Government developed an ambitious medium-term investment program intended to accelerate economic transformation and propel Cameroon into the group of fast-growing emerging countries. The Government is set to launch preparation of a new PRSP in early 2007. The new generation of the PRSP is expected to center on economic transformation and inclusive growth and to articulate a policy agenda that could pave the way for Cameroon to take off and get back on track to attain the Millennium Development Goals (MDGs) by 2015.